On the challenges of legal translation - Cao, Deborah (Comparative Legilinguistics, 2023)
This short commentary focuses on language and law and legal translation. It stresses the importance of language used in legal texts in the legal context and the complexities when more than one language is involved in interlingual and cross-cultural communication in law. There are age old challenges in legal translation as well as new ones in the digital age with the increasing use of machine translation systems. It is imperative today that human legal translators are familiar with machine translation tools and aware of how computer aided translation technologies process information and their strengths and weaknesses. To be able to effectively use machine translation systems should become a compulsory part of the digital literacy and skill sets of legal translators in the twenty-first century.